1999
DOI: 10.1038/sj.jp.7200269
|View full text |Cite
|
Sign up to set email alerts
|

Early Postnatal Dexamethasone Increases the Risk of Focal Small Bowel Perforation in Extremely Low Birth Weight Infants

Abstract: OBJECTIVE:We observed two clusters of spontaneous pneumoperitoneums in extremely low birth weight infants during the use of a protocol for early dexamethasone prophylaxis (EDP) for bronchopulmonary dysplasia from 1996 to 1997. During surgery, focal small bowel perforation (FSBP) was found in eight of nine cases. A retrospective study was designed to identify risk factors for FSBP in these extremely low birth weight infants. METHODS:A case-controlled analysis was performed using all infants born weighing Ͻ1001 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
78
1

Year Published

2001
2001
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(81 citation statements)
references
References 12 publications
2
78
1
Order By: Relevance
“…As previously described, breast milk appeared to reduce the severity of NEC. 2,6,26,27 Our multivariate analysis showed that in neonates who developed NEC, the reported use of breast milk decreased the likelihood that a neonate would require surgical treatment.…”
Section: Discussionmentioning
confidence: 79%
See 3 more Smart Citations
“…As previously described, breast milk appeared to reduce the severity of NEC. 2,6,26,27 Our multivariate analysis showed that in neonates who developed NEC, the reported use of breast milk decreased the likelihood that a neonate would require surgical treatment.…”
Section: Discussionmentioning
confidence: 79%
“…This is a dilemma that likely plagues all recent studies of NEC, since the diagnostic criteria for ileal perforations are not standardized and only one study has used histological criteria for the diagnosis of perforations in a clinical cohort. 2 In addition, proxies may not adequately reflect the true severity of illness or the therapeutic approach. Retrospective studies are also limited by incomplete data, and evaluation of interactions between drugs (like steroids and indocin) is better done prospectively.…”
Section: Limitations Of Datamentioning
confidence: 99%
See 2 more Smart Citations
“…3 In 1988, Aschner et al 4 described a case series of SIP in LBW infants and was the first to demonstrate SIP as a prevalent diagnosis in this emerging patient population. At the end of the decade, Gordon et al 5 and Garland et al 6 demonstrated that early postnatal steroid (EPS) exposure was associated with increased prevalence of SIP in extremely LBW (ELBW) infants. Since that time, two NICHD randomized controlled, multicenter trials involving EPS in ELBW infants have been halted by their safety review committees because of perforations in the treated cohorts.…”
Section: Introductionmentioning
confidence: 99%